2016
DOI: 10.12659/msmbr.900193
|View full text |Cite
|
Sign up to set email alerts
|

Association of HLA-DRB1 Gene Polymorphism with Risk of Asthma: A Meta-Analysis

Abstract: BackgroundThe relationship between HLA-DRB1 alleles and asthma is controversial. The purpose of this study was to evaluate the relationship between HLA-DRB1 alleles and risk of asthma.Material/MethodsWe searched PubMed, Chinese National Knowledge Infrastructure (CNKI), Wan Fang (Chinese) database, and Chinese Biomedical Medical databases (CBM) to find studies on the relationship between HLA-DRB1 alleles and risk of asthma. We calculated the pooled odds ratio (OR) and 95% confidence interval (CI) using STATA 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
9
0
2
Order By: Relevance
“…It is widely accepted that airway function is altered by LPS exposure [ 4 6 ]. Several studies have shown that LPS exacerbated bronchoconstrictive and inflammatory effects in patients and animal model with allergic asthma, and enhanced antigen-specific allergic responses in the airway, and the severity of asthma is associated with LPS concentration [ 7 12 ]. However, recent experiments and epidemiological studies show that LPS protects against asthma [ 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that airway function is altered by LPS exposure [ 4 6 ]. Several studies have shown that LPS exacerbated bronchoconstrictive and inflammatory effects in patients and animal model with allergic asthma, and enhanced antigen-specific allergic responses in the airway, and the severity of asthma is associated with LPS concentration [ 7 12 ]. However, recent experiments and epidemiological studies show that LPS protects against asthma [ 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that development of bronchial asthma is reported to be associated with HLA inheritance [11], concomitance of AD, HT, thymoma-associated MG, and possibly bronchial asthma, could be related to common HLA allele or haplotypes. Since autoantigen is presented on the surface of antigen-presenting cells with HLA-class I (cytotoxic effects of CD8+ T-cells) or HLA-class II (effector effects of CD4+ T-cells), common antigen may also be involved in multiple diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Other study stratified the study group according to age and revealed that DRB1*03, DRB1*04, DRB1*09, and DRB1*15 were associated with asthma in children. Subgroup analysis by ethnicity showed that DRB1*03 and DRB1*15 were associated with asthma in whites, and DRB1*07 and DRB1*14 were associated with asthma in Asians [ 24 ].…”
Section: Discussionmentioning
confidence: 99%